(untitled) (Ius Novum, 2025)
The subject of the article is an original presentation of the crime specified in Article 244c of the Penal Code. Based on the amendment to the Penal Code of 2022, which entered into force a year later, a new type of crime was introduced under Article 244c of the Penal Code. Pursuant to it, a perpetrator who avoids implementing a compensatory measure in favour of the injured party or a person closest to them is subject to imprisonment. The rationality of this solution raises fundamental doubts, as it ignores other regulations provided for in the Penal Code, as well as the fact that the person to whom a compensatory measure has been awarded may pursue it through civil enforcement.